-4(3n-4)=-56

Simple and best practice solution for -4(3n-4)=-56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3n-4)=-56 equation:


Simplifying
-4(3n + -4) = -56

Reorder the terms:
-4(-4 + 3n) = -56
(-4 * -4 + 3n * -4) = -56
(16 + -12n) = -56

Solving
16 + -12n = -56

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + -12n = -56 + -16

Combine like terms: 16 + -16 = 0
0 + -12n = -56 + -16
-12n = -56 + -16

Combine like terms: -56 + -16 = -72
-12n = -72

Divide each side by '-12'.
n = 6

Simplifying
n = 6

See similar equations:

| -25=-1-6(1+3x) | | k^3=144k | | -7(1+3p)=-70 | | 10x^2+40x+2=0 | | 8x^3+64=0 | | 3(2n+4)+5(3-2n)=7-2n | | -2=-7(4a+7) | | 3(2+5x)=-39 | | 6(8k+8)=0 | | 3-4x=0 | | y-4(3)=0 | | -3x+6=2 | | 64y^2+112y+49=0 | | -6=29x | | 4+7z=3z-20 | | y-3(3)=0 | | 4+7z=20-3z | | 2l+2w=264 | | 4v-5=17 | | 2l+2w=264(10w) | | (4x+8)(3x-2)=0 | | 2(0)+y=42 | | 1=y+3(y-9) | | 2.4=2.7 | | 25p^2-49p-2=0 | | 6(x+3)=3(2x+9)-9 | | 14x^2y^2+68xy^2-210y^2=0 | | 17k-12-4k-16k= | | 45z^2+56z-45=0 | | 4(0)+-2=-2 | | 10x-26=264 | | 3x-8x= |

Equations solver categories